Answer:
y < -2x - 4
Step-by-step explanation:
This is a guessing game. You just have to plug and chugg to find your answer.
Look at the table they gave you and plug in the x and y value into the given equations and see if they're true or not.
For example, I used the point x=-2 and y=1 from the table.
I plug that into y < -2x - 4 and got a false statement:
y < -2x - 4
(1) < -2(-2) - 4
1 < 4 - 4
1 < 0
this is false because one cannot be less than zero. Therefore this equation is the wrong one.
If you tried to plug in x=-2 and y=1 into the other 3 equations you'll see that they'll be correct.
the equation is y-y1 =m (x,x1)
Answer:
1/4
Step-by-step explanation:
To find the average rate of change we find
f(3) -f(0)
----------
3-0
We need to find f(3) = 1/4 (3)^2 -4 = 1/4 (9) -4 = 9/4 -4 = -7/4
f(0) = 1/4 (0)^2 - 4 = -4
f(3) -f(0)
----------
3-0
-7/4 - (-4)
---------------
3-0
-7/4 +4
-----------
3-0
-7/4 +4
-----------
3-0
-7/4 +16/4
----------------
3
9/4
---------
3
9/12
1/4
Answer:
3/4
Step-by-step explanation:
The x values are 0 and 3. Use the formula y2-y1/x2-x1
Plug in the x factors into the orginal equation. Should look like the equations below:
f(x)=1/4(0)^2-4 -------> -4
f(x)=1/4(3)^2-4 --------> -7/4Now plug it in to the formula we saved earlier.
-7/4-(-4)/3-0= -7/4+4/3= -7/4+16/4/3
Then simplify it.
9/4/3, and in this case we have a fraction in a fraction and when this happens just multiply the equation by the x variables reciprical which in this case the x is 3 so the equation is multiplied by 1/3 and you would get 9/12. Now simplify that and you get 3/4.